Design and analysis of channel reservation scheme in Cognitive Radio Networks. (February 2015) - Chakraborty, Tamal; Misra, Iti Saha
Abstract: The primary aim of a Cognitive Radio Network (CRN) is to provide higher spectrum utilization through an opportunistic usage of the licensed spectrum bands by the unlicensed Secondary Users (SUs). However, these SUs face unpredictable interruptions in their transmissions due to sudden arrival of the licensed Primary Users (PUs), resulting in either handoff or dropping instances. The channel reservation policy for the PUs is one such solution that reduces the probability of their interference, though at the cost of lower system throughput. This paper provides a complete study of the channel reservation scheme in a CRN. Initially, the system model is defined along with an architectural framework to address the practical constraints involved in implementing the channel reservation strategy. A novel design approach is then adopted to develop the mathematical models, followed by an evaluation of the network parameters to obtain a tradeoff between the decrease in interference and low spectrum utilization when some channels are reserved in the CRN. The optimal number of channels to be reserved is also determined. In addition, as a potential application of the channel reservation policy, an analytical framework is designed for the VoIP applications in the CRN, that highlights significant improvement in the VoIP call quality. Finally, an extensive analysis in the real-life like simulation models validates the inferences drawn from the mathematical models, recording over 50% improvement in the interference-free transmission of the SUs with the channel reservation scheme in the CRN.